2021
DOI: 10.1111/ijcp.14657
|View full text |Cite
|
Sign up to set email alerts
|

The evaluation of urinary incontinence in secondary school children and risk factors: An epidemiological study

Abstract: Urinary incontinence is an important problem in childhood one that can occur for neurogenic or functional reasons. 1 According to the new terminology suggested by the International Child Continence Association, incontinence is divided into two groups-continuous and intermittent incontinence. While enuresis in the intermittent incontinence group only means incontinence during sleep, 2 the term "daytime incontinence" is used for children who do not have urinary incontinence during the night but have the conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Key studies furthermore report a higher risk for children to get NE if fathers (RR = 7.1), mothers (RR = 5.2), or both parents (RR = 11.3) have been affected 10 . In DUI, findings are in line with NE, 1,70,89 with a higher prevalence of DUI history in family members of affected children. The same is evident in adults with DUI, 33,50 with respect to both SUI 38,52 and UUI 53 .…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…Key studies furthermore report a higher risk for children to get NE if fathers (RR = 7.1), mothers (RR = 5.2), or both parents (RR = 11.3) have been affected 10 . In DUI, findings are in line with NE, 1,70,89 with a higher prevalence of DUI history in family members of affected children. The same is evident in adults with DUI, 33,50 with respect to both SUI 38,52 and UUI 53 .…”
Section: Resultsmentioning
confidence: 85%
“…Selection of eligible papers were performed according to the PRISMA‐ScR document, with two independent authors for screening, full text assessment and inclusion (see Figure 1 for PRISMA 2020 selection flow diagram). Seventy‐six papers 1,10,30–103 were included. Eligible papers are summarized in Table 1, and information about candidate genes are summarized in Table 2.…”
Section: Methodsmentioning
confidence: 99%
“…The early onset of nocturnal TT (<30 months) was associated with early nocturnal continence and a lower rate of enuresis (31). Acikgoz et al (11) reported a relationship between urinary incontinence only during the day, monosymptomatic and non-monosymptomatic enuresis, and initiation of the TT process after one year of age. In this regard, Akis et al (32) showed that if the age of TT was late (> 24 months), the risk of enuresis was 3.04 times higher than in controls.…”
Section: Discussionmentioning
confidence: 99%
“…However, the pathophysiology is not fully understood (2,(7)(8)(9). Some aspects of the toilet training (TT) process have been associated with the occurrence of PMNE (10,11).…”
Section: Introductionmentioning
confidence: 99%